Violence experience among cis-gender women living with HIV in Atlanta, Georgia: impact on HIV-related health and their preferences for violence screening and support - Garbarino, Sophia C.; Anderson, Katherine M.; Carlson, Madelyn S.; Kokubun, Caroline W.; Ellison, Celeste K.; Hadera, Selaem; Kalokhe, Ameeta S.; Sales, Jessica M. (Frontiers in Public Health, 2025)
IntroductionPeople living with HIV (PLWH) experience multiple forms of violence at higher rates than the general population; however, research on experiences of violence among cis-gender women living with HIV (CWLH) mainly focuses on intimate partner violence (IPV), with inconsistent documentation across the literature. To begin improving trauma-informed practices in HIV care, we examined experiences of IPV, non-partner violence (NPV), hate crimes, and adverse childhood experiences (ACEs) among CWLH. We then explored experiences and preferences regarding violence screening and support services among CWLH.MethodsAs part of a larger study on violence experiences and screening among PLWH, 88 CWLH in Atlanta, Georgia, completed a cross-sectional survey on violence and mental health from February 2021 to December 2022 and provided consent for medical chart abstraction. A subgroup of 24 participants completed in-depth interviews on experiences and preferences related to violence screening. Univariate and bivariate analyses were used to assess violence prevalence and associations with mental health and chart-abstracted HIV outcomes. Thematic qualitative methods were employed for interview analysis.ResultsEvery participant (100%) experienced at least one form of violence in their lifetime, which included IPV among partnered CWLH (83.33%), NPV (96.51%), hate crimes (85.23%), and ACEs (80.68%). More than half of the participants (61.36%) met diagnostic criteria for at least one mental health condition. Multiple forms of violence had high co-occurrence with post-traumatic stress disorder, depression, viral suppression, and retainment in HIV care. Qualitative analysis revealed that most interview participants had discussed violence or trauma with a healthcare professional before, reporting a mix of positive and uncomfortable experiences. Participants offered diverse perspectives on improving the violence screening process, including recommendations on how, where, by whom, when, and how frequently screenings should occur.ConclusionMultiple forms of violence are highly prevalent among CWLH, with several found to be associated with mental health and HIV outcomes. This highlights the necessity for a trauma-informed approach within HIV care settings. Healthcare professionals should consider the unique needs and preferences of CWLH when screening for violence and providing support services. Doing so may improve mental, physical, and overall well-being throughout the HIV care continuum.